An Innovative Approach to Treat Incisors Hypomineralization (MIH): A Combined Use of Casein Phosphopeptide-Amorphous Calcium Phosphate and Hydrogen Peroxide-A Case Report - Stefano Mastroberardino; Guglielmo Campus; Laura Strohmenger; Alessandro Villa; Maria Grazia Cagetti (Hindawi Limited, 2012)
Molar Incisor Hypomineralization (MIH) is characterized by a developmentally derived deficiency in mineral enamel. Affected teeth present demarcated enamel opacities, ranging from white to brown; also hypoplasia can be associated. Patient frequently claims aesthetic discomfort if anterior teeth are involved. This problem leads patients to request a bleaching treatment to improve aestheticconditions.Nevertheless, hydrogen peroxide can produce serious side-effects, resulting from further mineral loss. Microabrasion and/or a composite restoration are the treatments of choice in teeth with mild/moderate MIH, but they also need enamel loss. Recently, a new remineralizing agent based on Casein Phosphopeptide-Amorphous Calcium Phosphate (CPP-ACP) has been proposed to be effective in hypomineralized enamel, improving also aesthetic conditions. The present paper presents a case report of a young man with white opacities on incisors treated with a combined use of CPP-ACP mousse and hydrogen peroxide gel to correct the aesthetic defect. The patient was instructed to use CPP-ACP for two hours per day for three months in order to obtain enamel remineralization followed by a combined use of CPP-ACP and bleaching agent for further two months. At the end of this five-month treatment, a noticeable aesthetic improvement of the opacities was observed.